Une éducation sentimentale ou le roman d’amour de Salammbô - Geneviève Mondon (Flaubert: Revue Critique et Génétique)
The transcription and study of Salammbô’s preparatory manuscripts enable us to retrace the genesis of the feminine character by highlighting her personal adventure.  The unpublished passages, the margins and interlinear additions contribute precious elements to the construction of the heroine’s love story and give it a more erotic tone, before Flaubert deletes, transforms or skillfully conceals these fugitive traces.  My research privileges Salammbô’s point of view, in so far as one can grasp this enigmatic figure.  By intentionally putting aside the main issues of the novel, the historic war of Carthage, the mythic battle between Tanit and Moloch, great History and mythology, battles and massacres, the focus is on the sentimental adventure, which, as the author well knows, is a must in a historic novel.  The account of Hamilcar’s daughter’s social milieu, the analysis of her psyche, her desires, dreams and beliefs, shed light on her life as a woman.  The study of an unpublished passage such as that of the dancer reveals the novelist’s will to create a seductive and active character.  The warriors are spectators of the characteristic “hero” epiphany clearly expressed by the lyric singing and the esoteric dance.  After meeting, Salammbô and Mâtho, both prey to amorous desire, seek each other, avoid each other and dream of each other.  Another unpublished passage records the young woman’s dream.  Experiences combining pleasure and suffering, the mystic union with the snake, the “baisade”, contribute to her sentimental education, but the final disappointment—the failure of desire—is the true revelation.